Conductive polymers and derivatives as recognition element for electrochemical sensing of food and drug additives: A brief perspective - Hassan O. Shoyiga; Omolola E. Fayemi (Heliyon)
Conducting polymers (CPs) are a distinct category of polymeric materials characterised by conjugated main chains that display adjustable electrical and optical properties. By regulating their doping states, these characteristics can be enhanced for many applications. CPs have demonstrated stability in aquatic conditions, rendering them suitable as electroactive and recognition elements in chemointerfaces and as electrode materials, particularly in water-based systems. This paper examines the use of CPs and CP-based nanocomposites in electrochemical sensors, specifically their application in identifying contaminants in food and pharmaceuticals. This research offers a thorough examination of the mechanics underlying CP-based electrochemical sensors, elucidating the origin of their detecting abilities and the characteristics that render them suitable for various applications. It encompasses the theoretical understanding foundation of electrochemical sensing, providing insights into the principal frameworks and prevalent conducting polymers and their derivatives utilised in sensor development. Alongside the concepts of electrochemical sensing, we examine diverse electroanalytical techniques, including chronoamperometry, cyclic voltammetry, electrochemical impedance spectroscopy, and differential pulse voltammetry, which are presented in a tabular format. These techniques are extensively employed for the detection and quantification of pharmaceuticals and food adulterants. We briefly highlight CP-based nanocomposites that improve sensitivity and reduce detection limits of these sensors, with this information compiled in a comprehensive table. In summary, electrodes constructed from CP-based nanocomposites typically exceed the performance of those built from pristine CPs. Nevertheless, additional systematic research is required to enhance the comprehension of the design and optimisation of nanocomposite-based electrodes for more effective sensing performance.